The Role of Lavender Aromatherapy in Improving Sleep Quality Among Third Trimester Pregnant Women : Result From Pre Experimantal Study - Daeri Daeri; Nila Widya Keswara; Rosyidah Alfitri (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Sleep disturbances in third trimester pregnant women are common and can be caused by factors such as increased fetal weight, shortness of breath, back pain, and fetal movements. These factors often disrupt the mother’s sleep, leading to inadequate rest. Lack of sleep during pregnancy can have significant consequences, affecting physiological aspects like activity levels, fatigue, body weakness, delayed recovery, instability in vital signs, and a weakened immune system. Furthermore, sleep disturbances may increase the risk of low birth weight babies and other complications. The aim of this study was to investigate the effect of lavender aromatherapy on sleep quality in third trimester pregnant women. The study utilized a pre-experimental method with a one-group pretest-posttest design to measure changes in sleep quality before and after the intervention. A quota sampling technique was used to select 20 participants, all of whom were in their third trimester of pregnancy. The Hamilton Anxiety Rating Scale (HARS) questionnaire was employed to assess sleep quality as the research instrument. Data analysis was conducted using the Wilcoxon rank test. The results showed a significant effect of lavender aromatherapy on sleep quality, with the Wilcoxon test yielding a p-value of 0.000 (p < 0.05). This indicates a significant improvement in sleep quality after the intervention. The findings suggest that lavender aromatherapy helps in enhancing sleep by calming and soothing the limbic system in the brain, which creates a sense of comfort, allowing pregnant women to sleep longer and more soundly. In conclusion, lavender aromatherapy is an effective intervention to improve sleep quality in third trimester pregnant women, as evidenced by the significant improvement in the study participants’ sleep quality after using the therapy.